Polythiourethanes Crosslinked with Dynamic Disulfide Bonds: Synthesis via Nonisocyanate Approach, Thermomechanical and Reprocessing Properties. Issue 7 (4th February 2021) - Ge, Wenming; Zhao, Bingjie; Liu, Weiming; Nie, Kangming; Zheng, Sixun
Abstract: Polythiourethanes (PTUs) crosslinked with dynamic disulfide bonds are synthesized via a nonisocyanate approach. First, a difunctional five‐membered cyclic trithiocarbonate (1 ) is synthesized via the reaction of diglycidyl ether of bisphenol A (DGEBA) with carbon disulfide (CS2 ). Thereafter, the step‐growth polymerizations of 1 with α, ω‐diamino poly(propylene oxide)s with various molar masses are carried out to obtain a series of linear poly(mercapto thiourethane)s. These linear poly(mercapto thiourethane)s are readily crosslinked upon formation of disulfide bonds, which are generated via radical coupling reaction with the side mercapto groups. These crosslinked PTUs can be tailored into the materials from thermosetting plastics to crosslinked elastomers, depending on the molar masses of α, ω‐diamino poly(propylene oxide)s. More importantly, these crosslinked PTUs display excellent reprocessing properties at elevated temperatures, which is attributable to the metathesis reaction of dynamic disulfide bonds. Abstract : In this work, the synthesis of polythiourethanes (PTUs) crosslinked with dynamic disulfide bonds via a nonisocyanate approach is reported. It is found that the PTUs can be tailored into thermosetting plastics and crosslinked elastomers. In addition, these PTUs display reprocessing and/or self‐healing properties, which are attributable to the metathesis reaction of dynamic disulfide bonds.